Peningkatan Kinerja Mesin Loading Arm dengan Total Productive Maintenance - Riza, M.; Firdaus, Alfa (Proceeding Mercu Buana Conference on Industrial Engineering, 2023)
Machines or equipment are the most important part of a work system. Machines require effective and efficient maintenance to be able to guarantee and support business processes so they can operate properly. Maintenance activities are the most important part of the company's business programs in both the manufacturing and service industries. The Middle East Gas Industry is one of the industries that runs gas service processes. Based on observations, it was found that the engine had a breakdown problem which resulted in the machine not being able to operate optimally. This study aims to analyze the factors that cause the machine to experience a break down and make improvements so that the engine performance increases. This study uses the Fishbone method and Total Productive Maintenance. The research object was carried out on the Loading Arm machine. The problems that occur are caused by damage to Swifel. Improvements are made by carrying out the TPM pillars, namely planned maintenance and focused improvement. The results of the study show that during the initial period of 2023 there will be no leaks in the seals thereby increasing the performance of the Loading Arm and increasing productivity.